PENGARUH KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI KANTOR SATPOL PP BATAM - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
The aim of this research are to analyze: 1) influence of leadership toward the work satisfaction 2) influence of leadership and work satisfaction toward the work discipline office Satpol PP Batam. Kinds of this research is causative descriptive research. Population is all employees (281 persons) in Satpol PP Batam. Sampling method is stratified propotional random sampling so that were selected 165 employees as the respondence. Descriptive analisys , analisys rule and regulation test and path analisys were used answer the research problem. Result this research proved that 1) leadership has significant influences toward the work satisfaction , 2) leadership and work satisfaction signifcant influence toward the work discipline.